2017
DOI: 10.1128/aem.00276-17
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of the Xenorhabdus nematophila Transcription Factor Lrp Promote Mutualism with the Steinernema carpocapsae Nematode Host

Abstract: Xenorhabdus nematophila bacteria are mutualistic symbionts of Steinernema carpocapsae nematodes and pathogens of insects. The X. nematophila global regulator Lrp controls the expression of many genes involved in both mutualism and pathogenic activities, suggesting a role in the transition between the two host organisms. We previously reported that natural populations of X. nematophila exhibit various levels of Lrp expression and that cells expressing relatively low levels of Lrp are optimized for virulence in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 64 publications
1
36
2
Order By: Relevance
“…In fact, lrp mutants are poorly transmitted, which cannot be explained by a deficiency in reassociation with nematodes, as we found that IJs emitted from group 2 infections carried as many bacteria as those from group 1 infections. This observation contradicts the prediction of Cao et al (22) but supports previous findings by Sicard et al (19). Low transmission of group 2 comes instead from a sharp decrease in nematode reproduction, which is in agreement with earlier experimental results (20, 22) and corresponds with the well-established detrimental effect of secondary variants in mass production of S. carpocapsae (32).…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…In fact, lrp mutants are poorly transmitted, which cannot be explained by a deficiency in reassociation with nematodes, as we found that IJs emitted from group 2 infections carried as many bacteria as those from group 1 infections. This observation contradicts the prediction of Cao et al (22) but supports previous findings by Sicard et al (19). Low transmission of group 2 comes instead from a sharp decrease in nematode reproduction, which is in agreement with earlier experimental results (20, 22) and corresponds with the well-established detrimental effect of secondary variants in mass production of S. carpocapsae (32).…”
Section: Discussioncontrasting
confidence: 52%
“…This observation contradicts the prediction of Cao et al (22) but supports previous findings by Sicard et al (19). Low transmission of group 2 comes instead from a sharp decrease in nematode reproduction, which is in agreement with earlier experimental results (20, 22) and corresponds with the well-established detrimental effect of secondary variants in mass production of S. carpocapsae (32). We also found that IJs emitted from group 2 infections have lower survival during dispersal compared to group 1 infections, which is probably yet another indication that infections initiated with lrp mutants constitute an unfavorable environment for S. carpocapsae , which is consistent with the study of Cao et al (22).…”
Section: Discussioncontrasting
confidence: 52%
“…Our third model entails population growth and death arising due to phenotypic switching. X. nematophila exhibits a phenotypic variation phenomenon termed virulence modulation, in which cells switch between mutualistic and pathogenic states ( 41 43 ). The IJ transmits X. nematophila from a niche in which it expresses mutualistic behaviors (the insect cadaver in which it supports nematode reproduction) to one in which it expresses pathogenic behaviors (the blood cavity of a newly infected living insect host) ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…( 1 3 ) These bacteria colonize in a specialized intestinal receptacle of the infective juvenile (IJ) form of the nematode, and together, they form an entomopathogenic complex that can infect and kill different insects. 2 , 4 6 To survive, the nematodes search for a susceptible insect host in soil, perforating the insect’s intestinal wall and migrating into the hemocoel. Once in the hemocoel, the nematode releases X. nematophila into the insect host’s hemolymph, and the bacteria produce immunosuppressive compounds and insect toxins to overcome the host immune system and kill it.…”
Section: Introductionmentioning
confidence: 99%